6y+8=3(2y+3)

Simple and best practice solution for 6y+8=3(2y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6y+8=3(2y+3) equation:


Simplifying
6y + 8 = 3(2y + 3)

Reorder the terms:
8 + 6y = 3(2y + 3)

Reorder the terms:
8 + 6y = 3(3 + 2y)
8 + 6y = (3 * 3 + 2y * 3)
8 + 6y = (9 + 6y)

Add '-6y' to each side of the equation.
8 + 6y + -6y = 9 + 6y + -6y

Combine like terms: 6y + -6y = 0
8 + 0 = 9 + 6y + -6y
8 = 9 + 6y + -6y

Combine like terms: 6y + -6y = 0
8 = 9 + 0
8 = 9

Solving
8 = 9

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 55*75-3= | | 141-4x=32x+21 | | 10x+2(-5x)=-6 | | 5-3(2x+4)=-6x+6 | | 3(x+4)=3x+11 | | 2800=.5s+1000 | | 2x+3=2x+7 | | 4(3-1)=2f+9 | | 20-p=3p | | 2(a-4)=2a+8 | | 4(a-6)=3(a+4) | | 2w+5=5w-25 | | 89-2x=10x-17 | | t+6*5t=7t*t | | 10+2x=17-3 | | 7x-3x+2=-8-8 | | 2x=3*(x+1) | | 2(x+10)=15 | | 3x^2+5x=x-1-x^2 | | 325x+385(35-x)=12575 | | 6x^2+3x-12=0 | | c^2+8c=k | | x+6*4=x-2*8 | | 3d+1=2(d+1) | | 8-10x=86-24x | | 26=79-9 | | 24x=-16x | | 3c=4-2c | | 2b=8-3b | | 8x+15=3x-35 | | 2x^3(9x^2+5y)= | | 3a=16-a |

Equations solver categories